(untitled) (Journal of Partial Differential Equations, 2020)
In the present paper an existence and uniqueness of solution of the nonlocal boundary value problem for the third order loaded elliptic-hyperbolic type equation in double-connected domain have been investigated. At the proof of unequivocal solvability of the investigated problem, the extremum principle for the mixed type equations and method of integral equations have been used.